Kajian Tanggul Pengendali Banjir di Kali Pengkol - Kota Semarang - Limbong, Benson Jhon Ferry; Wulandari, Dyah Ari (JURNAL TEKNIK HIDRAULIK, 2024)
The Pengkol River, situated in Meteseh, Tembalang sub-district of Semarang City, underwent three significant flood occurrences from January to February 2023. An approach involving a structural flood control system, specifically a levee, was suggested as a solution to this issue. The objective of this research is to establish the arrangement and highest elevation of the levee flood control and evaluate its effectiveness in mitigating floods. To determine flood hydrographs, a hydrological analysis was carried out using the Rainfall-Runoff simulation with the SCS Curve Number method. Additionally, a hydraulic analysis was performed using Unsteady Flow simulation with HECRAS 1D/2D hydrodynamic models to define the river body, water profile, inundation, and levee design. The hydrologic analysis indicates that the flood discharge for the 50, 100, and 200-year return periods are 209.5 m³/sec, 225.1 m³/sec, and 240.6 m³/sec, respectively. Based on the hydraulic analysis, the maximum water levels resulting from these return periods' flood discharges are +35.62 m (Q50 years), +35.77 m (Q100 years), and +36.43 m (Q200 years). The Q200 years of return period was chosen for 2D modeling because it resembles documented flood occurrences. Using the HECRAS 2D Unsteady Flow model, it was found that before the levee implementation, the flooded area within the residential zone spanned 9462 m², with a peak water level of +37.3 m. With the levee application, using an existing layout with a total length of 230 m and a top levee level of +37.5 m, flooding was effectively prevented, reducing the maximum water surface elevation to +37.17 m. This demonstrates the levee's effectiveness in preventing floods.Keywords:  levee, flood,  HECRAS 1D 2D model,  inundation. Unsteady flow.